Traduire la non-binarité et l’altérité de genre en science-fiction - Pierre Gabriel Dumoulin; Emmanuelle Lescouet (ReS Futurae)
Gender fluidity and non-binary gender are widespread in science-fiction. Authors can benefit from the diversity offered by gender to experiment with spelling, agreements, and pronouns. This diversity is addressed in many ways : the neutrality of non-binary protagonists, robotic sentient beings, or extraterrestrial beings whose bodies and cultures have no conception of the human’s body binary system. The authors’ creativity tasks translators and editors to take a stand on how to render the strangeness of the source text (from neologisms to socio-cultural and political structures) in the target text, insofar as it leads to non-standardized propositions. In this article, we explore the diversity of proposals for representing non-binary and gender neutrality in science-fiction. To this end, we'll focus on a comparative analysis of Martha Wells' Murderbot Diaries and Becky Chambers' Monk and Robot series, along with their French translations. We will contextualize this analysis by exploring the ways in which Anglophone and Francophone authors address gender and non-binarity in the works.